FACTORS ASSOCIATED WITH THE INCIDENCE OF ANEMIA IN PREGNANT WOMEN IN INDONESIA: ANALYSIS OF INDONESIAN HEALTH SURVEY (SKI) 2023 DATA - Putri, Jessica Reitanya; Pujonarti, Siti Arifah; Syafiq, Ahmad; Achadi, Endang Laksminingsih; Perkasa, Al Ilham Ksatria Gagah; Basrowi, Ray Wagiu (PT. Varians Statistik Kesehatan, 2025)
Anemia is a common nutritional issue among vulnerable populations, including toddlers, adolescents, women of reproductive age, and pregnant women. Anemia in pregnant women impacts both the mother and fetus. For the mother, it reduces quality of life and can lead to mortality. Babies born to anemic mothers are at risk of congenital abnormalities, stillbirth, and stunting. Maternal health issues during pregnancy affect the critical first 1000 days of a child's life, with permanent consequences for survival, necessitating appropriate interventions to minimize these risks. The 2023 SKI Report indicates a 27.7% prevalence of anemia among pregnant women in Indonesia, classified as a moderate public health issue. This study is a quantitative study using a cross-sectional design aimed to identify factors associated with anemia in pregnant women in Indonesia in 2023, utilizing secondary data from the 2023 SKI. The dependent variable was anemia, with independent variables from socio-demographic factors, lifestyle factors, dietary patterns, and pregnancy-related factors. Data analysis used complex samples, including univariate and bivariate analyses with chi-square tests. The study found significant associations between anemia in pregnant women and consumption of meat, poultry, and their processed products (p-value = 0.047), pregnancy interval (p-value = 0.033), and consumption of supplementary feeding (PMT) (p-value = 0.001) in Indonesia in 2023.